2020
DOI: 10.1101/2020.02.03.932939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beef cattle that respond differently to fescue toxicosis have distinct gastrointestinal tract microbiota

Abstract: Tall fescue (Lolium arundinaceum) is a widely used forage grass which shares a symbiosis with the endophytic fungus Epichloë coenophiala. The endophyte produces an alkaloid toxin that provides herbivory, heat and drought resistance to the grass, but can cause fescue toxicosis in grazing livestock. Fescue toxicosis can lead to reduced weight gain and milk yields resulting in significant losses to the livestock industry. In this trial, 149 Angus cows across two farms were continuously exposed to toxic, endophyte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(48 reference statements)
3
4
0
Order By: Relevance
“…7). The fecal microbiome of cattle grazing tall fescue also contains Proteobacteria, Euryarchaeota, and Lentisphaera phyla at abundances similar to those observed by us for the rumen (17,18,47).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…7). The fecal microbiome of cattle grazing tall fescue also contains Proteobacteria, Euryarchaeota, and Lentisphaera phyla at abundances similar to those observed by us for the rumen (17,18,47).…”
Section: Discussionsupporting
confidence: 80%
“…We compared our findings with the published information on the fecal microbiome of cattle that grazed tall fescue. In two studies where cattle were moved from a mixed ration to MaxQ and KY-31 in parallel (17,18) (17,18,47). Similar changes were observed in our MaxQ-1 to KY-31 shift (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Results for w1_7 were presented in the main text due to preliminary analysis using these data ( Koester et al, 2020 ) showed that the estimated additive genetic (2.22 [kg/wk] 2 ) and residual (1.09 [kg/wk] 2 ) variances during this period were greater than for the other periods, with 1.04 (kg/wk) 2 and 1.94 (kg/wk) 2 , respectively, for w7_13, and 0.58 (kg/wk) 2 and 1.09 (kg/wk) 2 , respectively, for 1_13, while having similar heritability estimate for these three time windows (~0.35). This is in accordance to reports showing that, under stress/disease conditions, traits show greater additive genetic and residual variances compared with the same traits under a “clean” environment ( Scanlan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%